Language and Consciousness in the poetry of the "Novisimos": Guillermo Carnero's Latest Poetry - Ignacio-Javier López (Studies in 20th & 21st Century Literature, 1992)
Guillermo Carnero's latest book of poetry, Divisibilidad indefinida, has recently appeared in Spain. In it, the reader witnesses, on the one hand, the reaffirmation of the poetic of the "novisimos": a self-conscious use of language, the presence of "culturalism," a distancing of language, a doubling of the poetic persona. On the other hand, the book reveals an effort to encompass a more complete perspective of poetic reality. The combative attitude of the first decade of the "novisimos" having been left behind, Carnero now develops his poetry in Divisibilidad indefinida by bringing it nearer to human life, although without renouncing the aesthetic imperatives indicated by his earlier work of Ensayo de una teoria de la visión.
Keywords: Novismos; Guillermo Carnero; poetry; Spanish poetry; Divisibilidad indefinida; self-conscious; consciousness; language; culturalism; poetic reality; Ensayo de una teoria de la visión